Sablot (Litsea Glutinosa), Lour Rob., in the Continuing Preservation and Conservation of the Cultural Heritage of Ilocos (Philippines): A Historic and Technical Approach - Norma A. Esguerra (SAMPURASUN, 2018)
Abstract Materials science and engineering improves crude tools and gadgets and enhances the productivity, effectiveness and efficiency of men. To do this, it discovers new sources of materials, Improves operations and performances at lower costs. This study aimed to promote the use of sablot in the conservation and preservation of the heritage structures of Ilocos, Philippines, and to demonstrate the structural feasibility of sablot paste as cement substitute. Interviews with selected senior citizens knowledgeable of the construction methods were conducted to determine the proportion of the aggregates and the sablot paste. From the interviews, samples were constructed to replicate the proportion original formulation of the sablot paste and aggregates. Records show that the churches of Ilocos were constructed earlier than the recorded date of invention of cement which was introduced to the world in 1824 by Joseph Aspdin, an English inventor. Indigenous materials were used for the construction of said Ilocos structures, like coral bricks made of sticky clay and molasses mixed with leaves and trunks of a tree called “sablot” soaked in water were used instead of cement. This fact then necessitates that in the preservation and conservation of the heritage structures, the original set of materials be used, thus, the need to replicate the mixtures done by the forefathers. This research compares the strength of original mixtures vis-à-vis the present-day set of reconstituted materials against that of cement, which invite a highly feasible “genuine” preservation and conservation procedure for the aging structures, instead of using modern methods. Keywords: Sablot, sablot paste, preservation, conservation, heritage Introduction Consciously or not, humans have to attribute their present convenience and progress from products, processes and inventions. It is materials science, also commonly known as materials science and engineering, that is responsible in improving crude tools and gadgets into things that would enhance the productivity, effectiveness and efficiency of mankind. Material science is an interdisciplinary field which deals with the study of matter and their properties well as the discovery and design of new materials. This relatively new scientific field involves studying materials through the materials paradigm (synthesis, structure,properties and performance). (http://www.wikepedia.en). On December 21, 1999, Vigan, then the capital town of Ilocos Sur, became a UNESCO-inscribed heritage site. As such, the local government has to preserve and conserve its culture which is composed of tradition, as well as its existing structures by virtue of a Memorandum of Agreement with the Government of the Republic of the Philippines, through the Department of Tourism, and the Government of Spain, through the Agencia Española Cooperacion Internacional, the . Presidential Commission for the Restoration, Conversion and Preservation of the Vigan Heritage Village. (http://tawidnewsmag.com/, by Tawid News Team, February 26, 2007) The need to preserve and conserve applies to the built environment- the houses, the monuments, the churches, and all other constructs which reveal the culture and history of Vigan’s rich and glorious past. However, the act of preservation and conservation may be done using the materials of today’s technology, or by the same materials present before. If today’s technology will be used, the method of preservation and conservation shall be with the use of cement with its sand and gravel combination for dilapidated brick walls, and similar items. If the genuine preservation and conservation shall be adopted, then, the original material make-up of the structures should be used, which were sablot ((Litsea Glutinosa), molasses and lime, to paste bricks together. This study desires to offer a genuine act of preservation and conservation by using the original binder of bricks, sand and lime; the sablot. The role of sablot , through a historic and technical approach, should be appreciated as it has once shaped the cultural heritage of Ilocandia, buried in its antique, baroque churches and structures. This study also aims to substantiate binding characteristics of sablot unexplained by the forefathers through initial, experimental studies to perpetuate its legacy in the conservation and preservation of the cultural heritage of Ilocandia, the land of frugal and caring Ilokanos of Northern Philippines Literature Review The researcher used the historical and experimental methods of research to undertake the study. The historical type of research was used to recount the use of sablot (Litsea glutinosa) when it was used as binder for bricks and as a plaster to cover the brick surface over the centuries prior to the cement age. It was presented through documentation and interview to capture the cultural essence of the indigenous material. The technical approach to this research utilized the conduct of experiments to reconstitute the sablot paste based from the interviews with senior Ilokano citizens. Through this, the researcher could formulate a first hand experience with the sablot paste described from the interviews. Three (3) samples with sablot paste were extracted from a demolished antique fence. Their strength, measured by the ultimate compressive stress, fc’ were compared with the ultimate compressive strength of hollow blocks today. Three (3) cylindrical concrete samples, 6” in diameter, 12” long, were prepared to compare how sablot fares with the same size as the concrete cylinders. The sablot samples, aside from comparing their strength with concrete, were also intended to determine the effect of the length of soaking time on their strength: five (5) samples (Group A) with the sablot paste three (3) days old, and five (5) samples (Group B) with the sablot paste six (6) days old. The age of the sablot paste is the duration of its soaking time in water. Results and Discussion The procedures discussed earlier yielded the following findings: 3.1. The Historical Approach Paoay Church The Paoay Church is one testimony of the use of sablot as binder. Started in 1704, and inaugurated in 1896 (192 years in the making), the Spanish friars supervised the construction. (Vigan museum). Sta. Maria Parish Church Msgr. Roque Reyes, Parish Priest of the St. Paul Parish, Vigan City, Ilocos Sur during the conduct of this research, and Archdiocesan Curator of Nueva Segovia, also attested that the sablot leaves soaked in water develop a sticky substance that blends well with the aggregates for grouting and plastering. He has witnessed the sablot paste in the repair of the Sta. Maria Church where he was once the parish priest. The Sta Maria church is one of UNESCO’s enlisted World Heritage Sites - a baroque church. He further attested that twenty one (21) churches of Ilocos Sur were built using the sablot as binder. In the same interview with Mgsr. Reyes, the parish priest of Vigan during the conduct of this study, he claimed to have witnessed the repair of Sta. Maria church where was also a parish priest. According to him, the binding capability of sablot reveals that the soaking period would take 3 to 7 days in big earthen jars at 5-8 cu ft capacity (burnays in Iloko). The leaves were stored inside the jars, half-filled with water. The sablot solution would be taken out from the burnays to mix with the sand and lime aggregates. A proportion was followed for uniformity: two parts sand, one part lime, 1 part barisangsang, or unprocessed sugar. If not enough, the water component would again be replenished as the original amount in the same duration before it could bind again. This was done for two to three times at most, depending upon the state of the leaves’ decomposition. Almost all of the churches in Ilocos Sur and Ilocos Norte were built using sablot paste as binder for bricks. Thick masonry walls ranging from 1.0m to 1.5m define the periphery of the structures. Bantay Parish Church St. Augustine Church, the Parish Church of Bantay, Ilocos Sur, was constructed in 1590. Vigan Cathedral and Belltower According to testimonies of popular local aficionados in preservation and conservation led by Archt Rey Florentino in 2000, he well documented that sablot leaves were used as binder together with lime and the aggregates in the construction of big structures in the Ilocos, including that of the Vigan, the St. Paul Metropolitan Cathedral, in the early 1900š. San Juan (Ilocos Sur) Parish Church Some selected senior citizens of Ilocos Sur, confirm that sablot was used in the Ilocos Region as binder in building antique structures, particularly the churches which still stand today. They claim that centuries ago, old Ilocano builders used the solution where sablot leaves were soaked for days stored in old earthen jars called burnays, to bind bricks, sand, sugar and lime for grouting, then in plastering the bricks. Laoag City Cathedral Badoc Church Sinait Parish Church Indigenous materials were used for the construction. Coral bricks made of sticky clay and molasses mixed with leaves and tree trunks of a tree soaked in water or “sablot” were used instead of cement, granite or adobe stones. The mixture resulted in a sticky fluid which was then combined with lime from ashes of burnt shells. The bricks were pieced together with stucco, the mixture beaten to paste. All the labor was manual. http://www.philippinesmyphilippines.wordpress) Candon Church Sarrat Church Among the antique churches shown, no one of them was constructed earlier than 1824, the year when Joseph Aspdin introduced cement to the world. 3.2. The Technical Approach The technical approach used the experimental method of research. The composition of the sablot paste so described in the interviews was reconstituted and subjected to compressive strength tests so as to establish some first hand information about the construction material of the 16th century. In Table 1, three sablot samples were extracted from an old fence, and they represent original sablot mixtures, while the concrete samples represent modern structures. Table 1: Compressive Stress, Fc’ Values of Samples in MPa, using Sablot and Cement # Sablot Cement 1 1-3/4”x2-1/2”x6” 4.87 10.51 2 2-3/4”x3-3/4”x6” 11.86 22.12 3 2-3/4”x3-1/2”x7 9.82 10.31 Average 10.89 12.27 The concrete cylinders paired with the debris samples were molded from ungraded mixed aggregates hauled from the riverbanks of Banaoang Santa, Ilocos Sur. This should explain why the compressive stress results were low in contrast to the lowest fc’ used for concrete which is 17 MPa. The use of ungraded mixed aggregates was used to capture country-side construction which usually use ungraded mixed aggregates to make small bungalows or one-storey residential houses. When the strengths of the samples made of sablot paste were compared to the strength of the concrete samples, a t-value of 0.267 was computed less than the significant value of 0.802, making it not significant. This suggests that the fc’ values of the samples out of sablot paste are as strong as those of cement. Table 2 shows the strengths in terms of the ultimate compressive stresses of the samples mixed by the 3-day old sablot paste Table 2. Compressive Strength of Samples with 3 days soaking time (Group A) Sample # Fc’, MPa (psf) 1 0.81 (16,884.6) 2 0.83 (17,301.5) 3 0.80 (16,676.2) 4 0.78 (16,259.3) 5 0.82 (17,093.0) Average 0.808 (16,843.0) Table 3 similarly reveals the strengths measured in terms of the ultimate compressive stress of the samples mixed with 6-day old sablot paste. Table 3. Compressive Strength of Samples with 6 days soaking time (Group B) Sample # Fc’, MPa (psf) 1 0.95 (19,802.9) 2 0.90 (18,760.7) 3 0.94 (19,594.5) 4 0.93 (19,386.0) 5 0.91 (18,969.0) . Ave 0.926 (19,302.7) The results of the compressive tests show that the samples in Group B resisted relatively higher stresses than those in Group A. Apparently, the length of soaking time affects the strength of the resulting mixture. The samples of Group B were 244 days old. The sablot paste where the leaves were soaked in clean water was six (6) days old. When the fc’ values of the two groups of samples using the soaking time of 3 days and 6 days as variable were analyzed, the t-value computed (t = -9.329) was less than the significant value of t at .000. Therefore, the soaking time is significant. This further suggests that the soaking time affects the strength of the samples. The samples in Group B molded using the sablot paste six (6) days old are stronger than those samples molded with sablot paste three (3) days old. It was observed further during the experiment that in three days time, the leaves soaked in water started to exude white sticky substances called latex. This reaction with water lasted only for seven (7) days, since all the latex are dissolved as the leaves start to disintegrate. The most sticky sablot paste occurred from the 3rd to the 6th day. When mixed with sand and lime the resulting mixture became fluid and plastic, similar in appearance and manageability as the present-day concrete mixture. After the 7th day, the sablot solution loses its binding power. Economics of the Sablot Paste A practical financial analysis is hereby conducted to convince the potential taker of this proposed technology. Being affordable and readily available are two of the major considerations in endorsing the sablot to solve housing problems for the rural poor. The proponent came up with the findings presented subsequently. A one square meter wall panel is taken as the subject of comparison. Its thickness is set to be uniform at one inch on both sides, internally and externally. The proportion of the concrete plaster and its area of coverage shall also be the wall coverage of the plaster using sablot as binder. The volume per mix is 0.085 cu.m. The coverage area for this volume of plaster is 1.8 sq.m. The sablot paste contains one part lime and two parts sand, practically yielding the same volume of mixture as the cement plaster and the same coverage of plastered area. The cement plaster uses an approximate volume of 25-30 liters of water to mix the aggregates for every bag of cement. The same volume of water is also the same volume of sablot solution needed to mix the aggregates in the preparation of the sablot plaster. By comparing estimates with the cement and sablot plaster, (refer to Table 4) the cement plaster incurs a total expenditure of P 264 for every one square meter of area plastered, while the sablot plaster only incurs a minimum expense of P171.50 for the same area, using current market prices during the conduct of this research. Table 4. Comparative Estimate on the Use of Cement and Sablot as Wall Plaster Qty Unit Cost Cement Plaster Compo-nents Unit of Measure Total 1 230 Portland Cement bag 230 0.057 600 River Sand Cu,m, 34 Total 264 Qty Unit Cost Sablot Plaster Compo-nents Unit of Measure Total 0.5 275 Lime Bag 137 0.057 600 River Sand Cu.m. 34 171.50 Conclusion In view of the findings solicited from the study, the experiments conducted suggest that: a) the sablot paste is as strong as cement within ordinary loadings, b) the age of the sablot paste has a significant effect to its strength. The Ilocos churches are testimonies of the capability of the sablot solution to bind the construction aggregates used during the pre-cement eras, Therefore, its use could be continued and adopted, to carry on a genuine preservation and conservation of the heritage structures. Recommendation There is a need to bring back the sablot to the locality not only of its potential as an alternative to cement but also due to its folkloric importance in the shaping of the Ilocano culture. The construction industry is never complete in itself by the present technology. It should also acknowledge the basic foundation provided by those of the past anchored in the old churches. More experiments should be conducted to explore more possible uses of sablot as a construction material, e.g. its capability when used to resist moment, or shear. More studies be conducted to hasten its settling and curing time, as well as to formally establish its reaction and bond when mixed with cement. A modern technique of using sablot should be studied to make its use more adoptable. Acknowledgment The author is deeply grateful toDr. Edelyn Cadorna, Director, Research and Statistical Assistance Center (RSAC), University of Northern Philippines, Vigan City, for extending her technical expertise in the statistical analysis of this study. References http://www.philippinesmyphilippines.wordpress) (http://tawidnewsmag.com/, by Tawid News Team, February 26, 2007) (http://www.wikepedia.en). Archt. Florentino, Rey, Documentation of Ilocos Churches during the inception of Vigan City as World Heritage Site by UNESCO, 2000 Vigan City Museum Interviews with senior citizens Interview with Msgr. Roque Reyes, Parish Priest of St. Paul Parish, Vigan City, Ilocos Sur and Archdiocesan Curator of Nueva Segovia